Periodontal heath in first trimester of pregnancy and birth weight outcomes - Varsha Christy Rani Balaji; K Saraswathi; S Manikandan (Wolters Kluwer Medknow Publications, 2021)
Introduction: The oral microbiome is influenced by numerous immediate environmental factors including pH, anaerobic conditions, nutrition, and hormone levels. During pregnancy, due to the associated hormonal changes, periodontal tissues show an enhanced inflammatory response to plaque microbiome. This is mediated by female sex hormones that are drastically altered in pregnancy. This study was undertaken to estimate the association of birth weight and the influence of the oral periodontal health in pregnant women in Chennai, South India and correlate the same with education and body mass index (BMI). Methods: This was a controlled, minimal interventional, prospective, observational study to identify the relationship of gingival health in the first trimester of pregnancy and on birth weight. Potential participants were referred by health-care providers. Pregnant women (≥18 years and ≤25 years) in the first trimester were enrolled for this study. Results: Of the 165 pregnant women, 121 pregnant women formed the study group. Conclusion: It was found that low birth weight could be a consequence of several modifiable and non-modifiable factors. This study shows the association of oral health of the mother in the first trimester with low birth weight. The findings of this study need to be confirmed with a large-scale, multi-centric study accounting for all known confounders. Till such a study is performed, the need for optimal oral health of an expectant mother cannot be discounted and there is no absolute harm in having good oral hygiene.